The influence of fiber bundle width on the mechanical properties of filament-wound cylindrical structures - Pourahmadi, Emad; Taheri-Behrooz, Fathollah (International journal of mechanical sciences, 2020)
•Three-dimensional modeling of repeated unit cell (RUC) in meso‑scale.•Effect of fiber bundle width on the behavior of the filament-wound composite pipes.•Comparison of three models of CLT, mosaic and fiber undulation.•Developing Python script to extract RUC properties. The fiber bundles crossovers, undulations and overlaps are inherent in the helical winding method of filament-would cylindrical structures such as composite tubes and pressure vessels. As a result, material properties will be highly affected because of the presence of these inherent defects in a structure. This research aims to evaluate the effect of these undulation regions on the local material properties and global mechanical performance of the tubes. In this article, a three-dimensional repeated unit cell (RUC) in a meso‑scale is developed to investigate the mechanical and thermal properties of the filament-wound composite tubes with different fiber bundle width. In this regard, three models of classical lamination theory (CLT), mosaic and fiber undulation were used and compared with each other. The given RUC is subjected to periodic boundary conditions (PBCs), and its mechanical and thermal behavior is studied by asymptotic homogenization theory (AHT). All the modeling steps are performed by an ABAQUS scripting interface (ASI) in the Python programming language. As an applied example, the effective material constants of a glass/epoxy tube with [ ± 45] lay-up are determined and the effects of different winding patterns are discussed. The results show that the fiber undulation model can cause up to 15.7% change in the mechanical and thermal properties of interweaved layers compared to the CLT. Moreover, the stress/strain distribution in a composite tube subjected to internal pressure is obtained. The findings of this article confirm that the global mechanical performance of cylindrical structures could be remarkably influenced by the local variations of the mechanical properties due to the fiber bundles crossovers/undulations/overlaps. [Display omitted]